2015
DOI: 10.3233/cbm-150507
|View full text |Cite
|
Sign up to set email alerts
|

HPV33 DNA methylation measurement improves cervical pre-cancer risk estimation of an HPV16, HPV18, HPV31 and \textit{EPB41L3} methylation classifier

Abstract: Abstract. BACKGROUND: Persistent infection with high risk human papillomavirus (hrHPV) types causes cervical cancer but most women who test positive are at very low risk of neoplasia. Strategies are needed which can retain high sensitivity of hrHPV testing but reduce the number of false-positives. We showed previously that a combination DNA methylation triage assay for HPV types 16, 18 and 31 and human gene EPB41L3 was useful to identify high grade cervical lesions. OBJECTIVE: Assess whether measurement of DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
77
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 49 publications
(80 citation statements)
references
References 23 publications
3
77
0
Order By: Relevance
“…We validated a DNA methylation classifier of CIN2+ histology, using hrHPV‐positive women from a UK screening group. The AUC obtained in this study was 0.78 (95% CI 0.69–0.88) compared with 0.82 (95% CI 0.80–0.84) in the colposcopy referral sample originally used to develop the classifier . The S5 classifier is a multibiomarker panel composed of a human gene EPB41L3 and the late regions of the four clinically most important HPV types: HPV16, HPV18, HPV31 and HPV33 .…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…We validated a DNA methylation classifier of CIN2+ histology, using hrHPV‐positive women from a UK screening group. The AUC obtained in this study was 0.78 (95% CI 0.69–0.88) compared with 0.82 (95% CI 0.80–0.84) in the colposcopy referral sample originally used to develop the classifier . The S5 classifier is a multibiomarker panel composed of a human gene EPB41L3 and the late regions of the four clinically most important HPV types: HPV16, HPV18, HPV31 and HPV33 .…”
Section: Discussionmentioning
confidence: 76%
“…The S5 classifier is a multibiomarker panel composed of a human gene EPB41L3 and the late regions of the four clinically most important HPV types: HPV16, HPV18, HPV31 and HPV33 . S5 performed significantly better than an alternative methylation classifier (S4) that lacked measurement of HPV33 . We further observed that the HPV33 component was more important than either HPV18 or HPV31 (Table ).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…S2), methylation of this region was assayed in the main study because of the importance of HPV18 as a carcinogenic HPV. To these assays we added biomarkers in the L1 region of HPV31 and the L2 region of HPV33, which were validated as informative in different studies …”
Section: Resultsmentioning
confidence: 99%
“…can be associated with cervical carcinogenesis (4147). Several Mycoplasma species infect eukaryotic cells, where they activate genes and have been associated with malignant transformations (14, 17, 48, 49).…”
Section: Discussionmentioning
confidence: 99%